Chemotaxonomy and diagenesis of aliphatic hydrocarbons in rice plants and soils from land reclamation areas in the Zhejiang Province, China - Mueller-Niggemann, C.; Schwark, Lorenz (Pergamon, 2015)
Rice is the most important staple food globally and requires large growth areas kept under flooded paddy conditions, contributing significantly to microbial greenhouse gas emissions. Biogeochemical cycling in such agroecosystems has been investigated intensively but molecular biomarker studies are scarce. We conducted a chemotaxonomic investigation of wax alkanes differentiated for plant tissue (leaf, stem, root) of rice and intercrop plants (maize, sorghum, rape, mustard, bean, cotton) and studied the incorporation of these lipids into soil under paddy compared with upland management forms. Soil chronosequences reflecting paddy and upland agroecosystem changes compared with natural soil substrates over the past two millennia were studied in land reclamation areas of Zhejiang Province, China. Soils evolved on tidal wetland sediments contained predominantly lipids derived from terrigenous supply by the Yangtze River (YR = Chang Jiang) and to a lesser extent from marine sources via the East China Sea (ECS). Agricultural usage converted lipid composition of topsoil within 50 yr to reflect the n-alkane patterns of crops with their relative proportion increasing with cultivation time. Alkyl chain length distribution of rice was broad compared with upland plants, due to the water regime changing over the growth period. This separated paddy from upland managed soils on the basis of alkyl lipids, allowing reconstruction of past land use change. Combustion of crop biomass after harvest is common practice and generates alkenes upon incomplete combustion which, due to their high reactivity, are immediately converted to alkanes with lower carbon preference index (CPI) in topsoil. The storage of lipids and organic matter over time is greater in paddy than in upland managed agroecosystems and contributes to CO2 sequestration from the atmosphere.